ANALISIS KOMPOS BERBAHAN BAKU SAMPAH PASAR TRADISIONAL KOTA MANADO HASIL TEKNOLOGI PENGOMPOSAN Accelerated Revolver Windrow Composting - Ade Rizkyany Patadjenu; Zetly E. Tamod; Diane D. Pioh; Marjam M. Toding (Universitas Sam Ratulangi, 2020)
ABSTRACTThe purpose of this research is to identify the composition of traditional market waste, todetermine the effectiveness of composting and to determine the mutrient content of the compostingtechnology of Accelerated Revolver Windrow Composting. Conducted in the city of Manado withdescriptive qualitative research methods where data analysis is devided into 3 namely indentificationof composition, composting effectiveness and compost content analysis. The result showed that : (1)identification of Pasar Bahu waste consisted of 84.21% organic waste from vegetables and 15.79%inorganic waste, Pasar Bersehati waste 91.67% organic waste from vegetables and 8.33% inorganicwaste; garbage Pasar Karombasan 89.72% organic waste from vegetables and 10.28% inorganicwaste; (2) The effectiveness of composting using mature compost parameters shows that composproduced has an average level of composting effectiveness of 90%; (3) The content of compostproduced by Accelerated Revolver Windrow Composting technology made from organic marketwaste and beef cattle feces after being compared with the nutrient content criteria can be categorizedwell and the value of the content is in accordance with the quality standars of organic fertilizer bySNI.Keywords: Compost, market waste, city of Manado, ARWC